Hybrid structure of zinc oxide nanorods and three dimensional graphene foam for supercapacitor and electrochemical sensor applications - Dong, Xiaochen (2013)
A hybrid structure of zinc oxide (ZnO) on three dimensional (3D) graphene foam has been synthesized by chemical vapor deposition (CVD) growth of graphene followed by a facial in situ precipitation of ZnO nanorods under hydrothermal conditions. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) are used to characterize the morphology and structure of graphene/ZnO hybrids. The results show that the ZnO nanorods have high crystallinity and cluster uniformly on graphene skeleton to form flower-like nanostructures. Serving as a free-standing electrode, the electrochemical and biosensing performance of graphene/ZnO hybrids are studied by cyclic voltammetry, electrochemical impedance spectroscopy, galvanostatic charge–discharge and amperometric measurements. It is found that the graphene/ZnO hybrids display superior capacitive performance with high specific capacitance (~400 F g−1) as well as excellent cycle life, making them suitable for high-performance energy storage applications. Furthermore, the graphene/ZnO hybrids exhibit high sensitivity for detection of [Fe(CN)6]3+ and dopamine, with the extrapolated lower detection limits of ~1.0 μM and ~10.0 nM respectively. These results demonstrate the potential of free-standing graphene/ZnO hybrid electrodes for the development of highly sensitive electrochemical sensors.